Identifying the influence of the concentration of surfactants on the technological indicators of aerosol emulsion - Putyatin, Bogdan; Bliznjuk, Olga; Masalitina, Nataliia; Bezpal’ko, Valentyna; Zhukova, Liubov; Filenko, Olesia; Horiainova, Viktoriia; Ponomarova, Maryna; Ryabev, Anton; Beliuchenko, Dmytro (Eastern-European Journal of Enterprise Technologies, 2024)
The object of the study is an emulsion system containing emulsifiers (Emulgin B2, Lanett SX), wetting agents (propylene glycol, glyceryl cocoate) and sodium laureth sulfate as a foaming agent. The main problem solved in the study is to ensure rational technological properties of emulsion systems in aerosol form under variable storage and use conditions. The results obtained showed that to ensure maximum emulsion stability during 7 and 30 days of storage, the optimal concentrations of Emulgin B2 are 2.75…3.0 %, and Lanett SX is 2.0…2.5 %. To achieve the desired foaming ability (80…85 %) and foam stability (75…80 %), it is recommended to use sodium laureth sulfate at a concentration of 0.20…0.22 %. It was found that the wetting agents – propylene glycol (7 %) and glyceryl cocoate (1.5 %) – provide optimal system viscosity within 35…40 mPa·s. The stability of the emulsion is ensured by the formation of strong interfacial films using Lanett SX, while Emulgin B2 improves the thermal stability of the system. Foaming properties are provided by the ability of sodium laureth sulfate to reduce interfacial tension, however, too high concentrations can lead to foam oversaturation and deterioration of its stability. The features of the obtained results are that specific concentration limits of the components are justified, at which the necessary stability and functionality of the emulsion system are ensured. This allows solving the problem of achieving optimal characteristics of the emulsion system during storage and use, ensuring comfortable application to the skin and a stable foam structure. The scope of application of the obtained results is the cosmetic industry